Application of The Icare Model to Improve Problem-Solving Ability in Momentum and Impulse Materials in Class X SMA - Utami, Alifia Mentari; Azhar; Yennita (RADINKA JAYA UTAMA PUBLISHER, 2022)
The purpose of this study is to determine the problem-solving abilities of students using the ICARE model and to determine the differences in problem-solving abilities. The type of research used is experimental research with a quasi-experimental design called